The Effect of Project-Based Learning (PjBL) Model on Students’ Science Literacy Skills - Qisthina, Rara Amalina; Listiani, Listiani; Nursia, Nursia (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
This study aimed to determine the effect of the application of Project-Based Learning (PjBL) model on students' science literacy skills at SMA Hang Tuah Tarakan. The study was motivated by the observed low levels of science literacy among students, attributed to a lack of exposure to tasks that require in-depth reasoning and critical thinking. Employing a quantitative approach with a quasi- experimental method, the study utilized a non-equivalent control group with a pretest-posttest design. The population consisted of all tenth-grade students at SMA Hang Tuah Tarakan, with purposive sampling used to select two groups: class X-A and class X-C, comprising a total of 52 students. Data on science literacy were collected through a multiple-choice test instrument. Data analysis included prerequisite testing (normality and homogeneity tests), hypothesis testing, and N- Gain testing to measure improvement. The hypothesis was tested using an Independent Sample T-Test, which revealed a significant difference in science literacy skills between the experimental and control groups, with a Sig. (2-tailed) value of 0.020, which was less than the significance level of = 0.05. These findings demonstrated that the application of the PjBL model had a positive effect on enhancing students' science literacy skills.